The Economics of Social Media - Guy Aridor; Rafael Jiménez-Durán; Ro'ee Levy; Lena Song (Center for Economic Studies and ifo Institute (CESifo), 2024)
We review the burgeoning literature on the economics of social media, which has become ubiquitous in the modern economy and fundamentally changed how people interact. We first define social media platforms and isolate the features that distinguish them from traditional media and other digital platforms. We then synthesize the main lessons from the empirical economics literature and organize them around the three stages of the life cycle of user-generated content: (1) production, (2) distribution, and (3) consumption. Under production, we discuss how incentives affect content produced on and off social media and how harmful content is moderated. Under distribution, we discuss the social network structure, algorithms, and targeted advertisements. Under consumption, we discuss how social media affects individuals who consume its content and society at large, and discuss consumer substitution patterns across platforms. Throughout the review, we delve into case studies examining the deterrence of misinformation, segregation, political advertisements, and the effects of social media on political outcomes. We conclude with a brief discussion on the future of social media.
Keywords: L82; L96; P00; D60; 330; social media; media economics; user-generated content